Assessment of the Combined Effects of Heavy Metal Cobalt and Sublethal Radiation on the Immune System - Gulzhan Ilderbayeva; Aigul Utegenova; Oralbek Ilderbayev; Zhibek Sembaeva; Gulsum Askarova (Biomedical and Biotechnology Research Journal)
Background: The purpose of the study was to examine the effect of a sublethal dose of ionized radiation and a toxic dose of cobalt and their combined effect on the state of immunity in laboratory rats, as a biological object of research. For this purpose, three experimental and one control group of animals are formed on the principle of pairs of analogues to examine these factors. Therewith, immunological research methods are used. Methods: The main immunosuppressive manifestation of the toxic dose of cobalt on the humoral component of the immune response is noted. Results: There is a decrease in the concentration of immunoglobulins (Igs) of the main classes in blood serum by 17%–30% (P < 0.05). A combined negative effect of both factors is observed on the activity of humoral immunity. As a result, the serum levels of Ig A in Group 3 animals are reduced by 30.5% (P < 0.05), Ig M – by 35.7% (P < 0.05), and Ig G – by 30.7% (P < 0.05) compared with the control group. Conclusion: Thus, the conducted studies allow determining the dependence of the immunosuppressive state of the urban population of Kazakhstan on a number of factors in a deteriorating environmental situation.